Pengembangan LKPD Berorientasi Pendekatan Saintifik untuk Meningkatkan Keterampilan Proses SAINS Siswa Kelas V - Pingsi Anggriani; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to develop LKPD oriented scientific approach in improving students' science process skills and determinity the feasibility, practicality and effectiveness of LKPD on the material properties of objects. The research and development procedure used the ADDIE model which was: analysis, design, development, implementation and evaluation. The results of the study based on the validator's assessment of the material aspect obtained an average score of 0.85, the language aspect is 0.86 and the media aspect is 0.89. From these three aspects, the overall average is taken, the value of 0.86 is obtained in the very valid category. The results of student responses to the product obtained an average score of 81.56 in the very practical category. While the results of the effectiveness show that the scientific approach-oriented worksheets are very effective in improving students' science process skills. Based on the results of the assessment, it can be concluded that the scientific approach-oriented worksheets developed are very valid, practical and effective for use in the science learning process in improving students' science process skills.